The impact of material deprivation and socioeconomic inequalities on the mental health outcomes of children and adolescents - Zaneva, M (2023)
Poverty and inequality are well-evidenced risk factors for mental health, though most of what we know is based on adults in high-income settings. This thesis contributes to efforts to better understand these risks for children and adolescents globally, for whom early intervention might be particularly important. Through a series of mixed-method studies in diverse datasets, the work in this thesis advances our understanding of how poverty and inequality are conceptualized, how they may impact mental health, and what potential interventions may be suitable to address both problems simultaneously. First, Chapter 1 provides a theoretical overview of the concepts of poverty and inequality and the potential mechanisms through which they may affect mental health, with a particular focus on children and adolescents. Second, Chapter 2 charts how the concept of socioeconomic status is defined and operationalized in a critical literature review, arguing that the wide heterogeneity of specific measures used poses important challenges for transparency, understanding of mechanisms, and ultimately appropriate intervention selection. Next, in a large cross-national survey, Chapter 3 zooms in on hunger as a measure for individual-level deprivation and investigates its relationship with mental health, providing evidence for the negative associations between hunger and worrying and suicidality, in addition to stable gender differences, with girls reporting more mental health problems. Then, Chapter 4 broadens out beyond the individual level and examines how country-level indexes for inequality and poverty relate to children and adolescents’ mental health through a multiverse analysis, further corroborating the negative associations between hunger and mental health, and higher frequencies of reporting mental health problems for girls. Finally, Chapter 5 explores one candidate intervention to improve mental health: cash transfers and monetary programs. A systematic review and metaanalysis support small but positive and significant effects of these programs on child and adolescent mental health. Overall, I argue that poverty and inequality can be captured via different specific measures, though relationships may differ in magnitude and significance; that consideration of sub-group effects, such as by gender, is important; that children and adolescents’ own perspectives are often critically left out from informing such choices and their further inclusion should be a priority. Across my work, I find that poverty and inequality are neither unmeasurable, nor unmodifiable. There are effective interventions, such as cash transfers, that can not only improve the material circumstances of young people, but also improve their mental health. As such, I hope my work can contribute to broader efforts that bring us closer to a world without childhood poverty and with better mental health for all.